Scour due to turbulent wall jets downstream of low-/high-head hydraulic structures. Issue 1 (31st December 2016) - Hafez, Youssef I.
Abstract: To overcome over-prediction of the scour depths by existing methods, a mathematical model is developed based on a work transfer theory. This model predicts the equilibrium scour hole's depth and length due to two-dimensional turbulent wall jets downstream of low-/high-head hydraulic structures. The work transfer theory states that the work done by the attacking jet flow is transferred to work done to remove the volume of the scoured bed material out of the scour hole. This results in an analytical nonlinear equation for predicting the equilibrium scour depth. This unique feature of the nonlinearity of the developed equation shows the mutual dependence of the scour geometry and flow hydrodynamics on each other. Non-circulating wall jet flows and re-circulating jet flows within the scour hole are both considered. A separate equation is developed for predicting the length of the scour hole. Field data at the Nile Grand Barrages in Egypt and the Shimen Arch Dam in China are used to validate the developed model. The developed equation was checked against laboratory data for scour downstream of a spillway for which a complete data-set exists. For scour downstream of grade control structures, an equation was derived from the low-head hydraulic structure equation and tested against laboratory data.